Necrotizing pneumonia in pediatric intensive care unit: A case series - Shreeshail V Benakanal; G M Manoj; K G Vikas; B Manjula (Wolters Kluwer Medknow Publications, 2023)
Necrotizing pneumonia (NP) is a rare and severe complication of bacterial community-acquired pneumonia associated with high morbidity and mortality rate. We present a case series admitted in the pediatric intensive care unit (PICU) of our tertiary care hospital for 6 months. Five cases (positive blood culture) were selected based on the features of pneumonia with moderate-to-severe respiratory distress at admission. All cases are treated with antibiotics (piperacillin/tazobactam and vancomycin) as per blood culture and sensitivity results and oxygen therapy by high-flow nasal cannula/mechanical ventilation based on the decision of the treating physicians. Intercostal drainage tube was inserted for all empyema/pneumothorax cases. Decortication was done in two cases. Out of five cases, three cases were recovered after prolonged treatment in PICU and two cases succumbed to death in the 2nd week of hospitalization. Treatment of necrotizing pneumonia should be initiated early with broad-spectrum antibiotics along with staphylococcal cover till culture reports are awaited.